Peningkatan Teknologi Dalam Pembelajaran Guru Terhadap Perkembangan Merdeka Belajar Di Tingkat Sekolah Dasar - Saragi, Christina Natalia; Ndraha, Libertini Priskila; Marbun, Friscilia; Nainggolan, Dewinarto; Manik, Elva Cecilia; Samosir, Eren Octavia (Pusat Riset dan Inovasi Nasional, 2023)
To improve the quality of teacher education and encourage the establishment of the merdeka learning system at the elementary school level, technology plays an important role. The educational concept called Merdeka Learning provides opportunities for students to choose and organize educational programs according to their interests and needs. Technology is now very capable of supporting the integration of independent learning into classroom practice in this digital era. Technology integration in teacher learning has a positive impact on improving the quality of learning at the elementary school level. Teachers who are trained and assisted in the use of technology can create learning content that is more interesting and interactive. In addition, technology also gives students the freedom to organize their own learning and choose learning resources according to their individual interests and learning styles. This research provides great benefits for teachers and students in elementary schools. Teachers can use technology to improve the quality of learning, while students feel the freedom in learning that is more personal and according to their interests.